Manajemen Sumber Daya Manusia (SDM) dan Manajemen Komunikasi Kesehatan dan Manajemen Komunikasi Kesehatan di Dinas Kesehatan Kabupaten Rokan Hilir - Riauni Syaputri; Budi Hartono (Komunika : Jurnal Ilmiah Komunikasi, 2023)
This study is a literature review study that aims to examine the strategic role of Human Resource Management (HR) and Health Communication Management in improving the effectiveness of organizational performance, especially in the health sector. Based on a review of various sources, it was found that the success of an organization is highly dependent on the suitability of workforce placement with their field of expertise, as well as the effectiveness of internal communication in supporting program coordination and implementation. This study highlights a number of field findings that indicate a mismatch between the educational background of health workers and the job positions they occupy, which has the potential to reduce organizational performance and efficiency. In addition, weak communication management contributes to a lack of understanding of tasks and duplication of work. Therefore, the integration of proper HR management and effective communication management is key to creating an organization's competitive advantage. This study recommends the need for competency-based HR planning, supported by a structured and participatory communication system, to encourage employee performance and the quality of health services.